Síntese, caracterização e estudos espectroscópicos de redes de coordenação híbridas contendo lantanídeos - Rodrigues, Marcelo Oliveira (2007)
In this work is presented the hydrothermal synthesis, the structural studies and spectroscopic properties of three coordination polymers based on lanthanides ions (Eu3+, Tb3+ and Gd3+) and DPA as ligand (DPA= 2,6- dipicolinate). Structural study of [Eu(DPA)(HDPA)(H2O)2.4H2O] displayed the presence of self-assembled dimeric and hexameric water clusters fit in the linear chains and the respective role on the stabilization of supramolecular strucuture. The spectroscopic investigations show the low quantum efficiency (η = 12.7%) caused by large contribution of non-radiative decay rates governing the relaxation process due to vibronic coupling with water molecules. The coordination polymers [Tb(DPA)(HDPA)] and [Gd(DPA)(HDPA)] are isostructurals and allowed the investigation about energy transfers processes. In the case of [Tb(DPA)(HDPA)] compound, the photoluminescence data shown the high quantum yield of emission (≈ 50%) due tho the DPA ligand to be a good sensitizer and the lack of water molecules coordinated directly to metal.